Imagination and its role in research and knowledge: the metaphor in the new scientific spirit (2021)
The following writing is product of the discussions that the group of philosophical reflection of the UCPR has come realising during the past few years about from the knowledge. Starting off mainly of some important reflections of Gaston Bachellard, proposes that the language used by the classic method of investigation, the modern science and the scientific spirit, they are in trouble at the moment to provide explanations to problems that emerge these days, like those influenced by the NTIC´s and because of it, it is necessary to recognize that there is not only one way for the generation of scientific knowledge; which implies a new perspective about the reason in connection with imagination. From this discussion, they suggest to recover the metaphor in investigation, in such a way that what is presented as unnamable even in the language logical linear and syntactic, it can be reveal through poetical forms that anticipate what is to be in the new scientific spirit. It is tried, of this form, that the text motivates the present debate around the forms and elements in the knowledge generation and, that can serve as pretext for the academic and research discussion on the ideas presented here.